miRNA and its Dysregulation in Cancer Progression - Kaur, R.; Masih, R.L.; Kaur, J. (The Nucleus, 2022)
MicroRNAs [miRNAs] are conserved group of small, non-coding RNA involved in post-transcriptional gene regulation. Several studies have found that downregulation of miRNA after post transcriptional changes and negative effects on miRNAs acting as the activators of gene expression. Aberrant expression in body fluids of miRNA is a helpful diagnostic approach to early detection of cancer. Various mechanisms by which miRNA gets dysregulated include: dysregulation in miRNA biogenesis, abnormal transcription of miRNA, dysregulated epigenetic modification and genomic aberrations. Aberrantly expressed miRNA has been studied to affect the hallmarks of cancer. Modified miRNA causes some diseases which could be avoided or overcome by controlling miRNA gene expression. A novel biomarker by miRNA could be utilized for therapy purposes because miRNA controls certain gene expression in cases of cancer as well as some other ailments. In this review, we focused on the biogenesis and regulation of miRNA along with the dysregulation of it in human cancer and other diseases, along with highlighting some of the role of miRNA in therapy. By comparing previously studies, it is anticipated that miRNA based treatment would be one of the reliable and highly recommended to diagnosis or suppress cancer cells.